O papel da propaganda impressa para o desenvolvimento da compreensão leitora de textos multimodais no 9º ano do ensino fundamental - Sousa, Daniele Firmino Monteiro (2019)
This research aims to contribute to the development of the reading comprehension of students of the 9th year of Itapipoca public school in texts constituted of verbal and nonverbal language through the study of the genre printed advertisement. Based on an intervention proposal for reading teaching, the aim is to improve reading comprehension practices as well as to investigate how the reading of verbal and imagery texts contribute to the development of reading competence. Our study was based on the theoretical assumptions of the conception of reading in Kato (1984), Kleiman (2004, 2013) and Liberato (2007), and the concept of literacy in Soares (2003), visual literacy in Rocha (2008), reflecting on the notions of text in Koch (2012), considering the basic conceptions of the discursive genres referenced in Bakhtin (2016), Marcuschi (2011), Bazerman (2005), Maingueneau), multimodality in Dionísio (2005, 2014) and Vieira (2004) and approaching the propaganda genre as a contributory genre for the development of reading skills in Pinho (1990), Melo (2006), Sandmann (2003) and Silva (2015) ), in addition to the argumentative assumptions in Fiorin (2015). The present study resorted to the guidelines of the national documents that guide Basic Education: PCN and BNCC. In the end, based on the students' advances presented in the analysis data, we validate the hypothesis that the didactic work with texts consisting of verbal and non-verbal language such as the printed propaganda genre, related to social experiences and associated with reading strategies, can to present enunciative resources that contribute to the development of the understanding of multimodal texts. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001